BRAIN ACTIVITY MEASURED BY FUNCTIONAL MAGNETIC RESONANCE IMAGING (fMRI) IS RELATED TO PATIENT-REPORTED SEVERITY OF URGENCY URINARY INCONTINENCE - Tadic, Stasa D. (2010)
PURPOSE: To investigate the relationship between experimental neuroimaging and self-reported measures of urinary incontinence. MATERIALS AND METHODS: We evaluated 14 functionally independent, community-dwelling older women (> 60 years) who had moderate to severe urgency urinary incontinence. All underwent detailed clinical assessment (3-day bladder diary, 24-hour pad test, and quality of life assessment), urodynamic testing, and functional brain scanning. Brain activity during reported urgency was assessed using a method that combines fMRI with simultaneous urodynamic monitoring during repeated cycles of bladder filling/emptying. We used SPM2, a statistical parametric mapping program, to correlate brain activity with relevant clinical covariates, including number of urgency incontinent episodes, amount of urine leakage, and psychological burden as assessed by the Urge Impact Scale (URIS-24) questionnaire. RESULTS: Activity in rostral and subgenual anterior cingulate gyrus, insula, inferior frontal gyrus, orbitofrontal cortex, dorsal and posterior cingulate gyrus, parahippocampus, cuneus and parts of parieto-temporal lobe correlated positively with daytime incontinence frequency and urine loss. Different brain regions correlated with the psychological burden, and the associations were inverse: precuneus/cuneus and posterior cingulate gyrus, superior temporal, supramarginal, and transverse gyrus. CONCLUSIONS: Regional brain activity in the setting of self-reported urgency, as provoked by bladder filling, correlates significantly with the severity of incontinence in daily life as well as the associated psychological burden. Thus, observations made under experimental conditions correlate with patients’ real-life experience and suggest neural correlates of urgency incontinence symptoms that could be used as potential targets for future investigations.